High-heat-resistance PE composite plastic and preparation method thereof

By introducing hollow zirconium tungstate spheres, elolite nanotubes and maleic anhydride grafted polyethylene wax into ultra-high molecular weight polyethylene, high heat resistance PE composite plastics are prepared, which solves the problems of difficult melt processing and poor high temperature resistance in UHMWPE materials, and achieves better fluidity and high temperature resistance.

CN119842135AInactive Publication Date: 2025-04-18JIANGXI XULIAN NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510323787.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ultra-high molecular weight polyethylene (UHMWPE) materials are difficult to melt processing and have poor high temperature resistance, which limits their application in high temperature environments.

Method used

Zirconium tungstate hollow spheres and ellowite nanotubes are used as inorganic fillers, combined with maleic anhydride grafted polyethylene wax as compatibilizers, ultra-high molecular weight polyethylene is used as matrix resin, and high heat-resistant PE composite plastic is prepared by extrusion and granulation.

Benefits of technology

It improves the fluidity and high temperature resistance of ultra-high molecular weight polyethylene, significantly improves the thermal deformation temperature of composite plastics, and makes it more widely used in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-heat-resistance PE composite plastic and a preparation method thereof, and belongs to the technical field of plastics, the composite plastic comprises the following raw materials by weight: 88-94 parts of ultra-high molecular weight polyethylene, 3-7 parts of an inorganic filler, 3-5 parts of maleic anhydride grafted polyethylene wax, and 0.1-0.5 part of an antioxidant; the inorganic filler is a compound product of zirconium tungstate hollow spheres and halloysite nanotubes; zirconium tungstate hollow spheres and halloysite nanotubes are used as inorganic fillers, maleic anhydride grafted polyethylene wax is used as a compatibilizer, ultra-high molecular weight polyethylene is used as matrix resin, the inorganic fillers, the maleic anhydride grafted polyethylene wax and the matrix resin are mixed with an antioxidant according to a certain proportion, and the mixture is extruded and granulated to obtain the composite plastic. The thermal deformation temperature of the prepared composite plastic is greatly increased compared with that of ultra-high molecular weight polyethylene, and the mechanical property is also improved, so that the composite plastic product can be widely applied in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastics, and in particular relates to a high-heat-resistant PE composite plastic and a preparation method thereof. Background Art

[0002] Ultra-high molecular weight polyethylene (UHMWPE for short) usually refers to polyethylene with a viscosity-average molecular weight greater than 1.5 million. It is a thermoplastic engineering plastic with a linear structure. Compared with ordinary polyethylene, UHMWPE has many excellent properties. Its chemical corrosion resistance, low water absorption, hygiene and non-toxicity are unmatched by other engineering materials. The main products include fibers, films, pipes, plates, rods, porous materials and special-shaped materials, etc., which are widely used in aerospace, marine engineering, rail transportation, municipal construction, petrochemical, mining, metallurgy, electricity, new energy materials and other fields.

[0003] UHMWPE has good mechanical and physical properties and is widely used in various fields. However, its large molecular weight leads to long molecular chains, and the molecular chains are intertwined. This structure, which is different from other engineering plastics, makes UHMWPE have a large melt viscosity and is difficult to melt process. It also has the disadvantage of poor high temperature resistance, and its heat deformation temperature is generally around 85°C, which limits the application of ultra-high molecular weight polyethylene products in high temperature environments. Therefore, providing a PE composite plastic with high melt fluidity and good high temperature resistance is a technical problem that needs to be solved at present. Summary of the invention

[0004] The object of the present invention is to provide a high heat-resistant PE composite plastic and a preparation method thereof, so as to solve the shortcomings of the existing UHMWPE material, namely, the difficulty in melt processing and the poor high temperature resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A high heat-resistant PE composite plastic comprises the following raw materials in parts by weight: 88-94 parts of ultra-high molecular weight polyethylene, 3-7 parts of inorganic filler, 3-5 parts of maleic anhydride grafted polyethylene wax, and 0.1-0.5 parts of antioxidant.

[0006] Furthermore, the inorganic filler is a composite product of hollow zirconium tungstate spheres and halloysite nanotubes, and the mass ratio of the hollow zirconium tungstate spheres to the halloysite nanotubes is 1:0.1-1.

[0007] Furthermore, the preparation steps of the hollow zirconium tungstate spheres are as follows: S1. Dissolve anhydrous glucose in deionized water, stir for 30 min, transfer to a hydrothermal reactor with a polytetrafluoroethylene liner, react at 200 °C for 4 h, cool to room temperature, wash the obtained product with deionized water and anhydrous ethanol by centrifugation for 3 times, and dry the product at 80 °C for 5 h to obtain carbon spheres; S2. Prepare solution a with a concentration of 0.5 mol / L with zirconium oxychloride octahydrate and deionized water, prepare solution b with a concentration of 1 mol / L with ammonium metatungstate and deionized water, and add solution a and solution b to the deionized water under stirring. After the addition is completed, continue stirring for 10 hours and then add hydrochloric acid solution. Heat to reflux reaction for 48 hours, cool to room temperature and remove the supernatant. After the product is allowed to stand at room temperature for 7 days, add carbon balls, stir for 1 hour and then stand for 12 hours, centrifuge, and dry the centrifuged product in an oven at 60°C to obtain a precursor powder. Place the precursor powder in a muffle furnace and keep it at 500°C for 2 hours and 610°C for 10 hours, then cool it to room temperature with the furnace to obtain zirconium tungstate hollow spheres.

[0008] Anhydrous glucose was used as the raw material to prepare the carbon sphere template, and then the carbon sphere was dispersed in a mixture of solution a and solution b, so that zirconium ions and tungsten ions were adsorbed on the surface of the carbon sphere to form a carbon sphere / zirconium tungstate precursor composite structure, and finally the carbon sphere template was removed by calcination to obtain zirconium tungstate hollow spheres.

[0009] Furthermore, the dosage ratio of anhydrous glucose to deionized water in S1 is 6 g:40-60 mL.

[0010] Furthermore, the dosage ratio of deionized water, solution a, solution b, hydrochloric acid solution and carbon spheres in S2 is 25 mL: 50 mL: 50 mL: 125 mL: 0.6-0.8 g, and the concentration of the hydrochloric acid solution is 6 mol / L.

[0011] Furthermore, the heating rate in S2 is 1-5°C / min.

[0012] Furthermore, the preparation steps of the maleic anhydride grafted polyethylene wax are as follows: Add polyethylene wax and xylene into a reaction kettle, heat to 120°C and stir for 5 minutes, add benzoyl peroxide and maleic anhydride, react at 110°C for 3-5 hours, cool to room temperature after the reaction, add acetone, precipitate, filter, dry the filter cake, grind and sieve, and pass through a 200-mesh sieve to obtain maleic anhydride grafted polyethylene wax.

[0013] With xylene as solvent and benzoyl peroxide as initiator, maleic anhydride is grafted onto polyethylene wax, and with acetone as precipitant, the product is precipitated to obtain maleic anhydride grafted polyethylene wax.

[0014] Furthermore, the usage ratio of polyethylene wax, benzoyl peroxide and maleic anhydride is 10g:0.1-0.2g:0.5-0.7g.

[0015] Furthermore, the polyethylene wax is PEW-0320A, purchased from Nanjing Tianshi New Material Technology Co., Ltd.

[0016] Furthermore, the antioxidant is at least one of antioxidant 1010 , antioxidant 1076 and antioxidant 168 .

[0017] The method for preparing the above-mentioned high heat-resistant PE composite plastic comprises the following steps: Ultra-high molecular weight polyethylene, inorganic filler, maleic anhydride grafted polyethylene wax and antioxidant are fully mixed and added into a twin-screw extruder, and extruded and granulated at 135-220°C to obtain a high heat-resistant PE composite plastic.

[0018] Beneficial effects of the present invention: The invention uses hollow zirconium tungstate balls and halloysite nanotubes as inorganic fillers, maleic anhydride grafted polyethylene wax as a compatibilizer, ultra-high molecular weight polyethylene as a matrix resin, and an antioxidant in a certain proportion, and extrudes and granulates to obtain a composite plastic, wherein the anhydride groups in the maleic anhydride grafted polyethylene wax molecular chains can interact with the inorganic filler surface groups to improve the dispersibility of the inorganic filler in the matrix, and the long polyethylene wax molecular chains can improve the fluidity of the ultra-high molecular weight polyethylene through lubrication and disentanglement. The hollow zirconium tungstate balls with a spherical structure and the halloysite nanotubes with a hollow tube structure are uniformly dispersed inside the ultra-high molecular weight polyethylene, and the two cooperate with each other to form a complex network structure. When the composite plastic is subjected to the external temperature, the movement of the ultra-high molecular weight polyethylene molecular chain is hindered, thereby improving the high temperature resistance of the composite plastic. The hollow zirconium tungstate balls and the halloysite nanotubes themselves also have good heat resistance, which can hinder heat transfer and help improve the temperature resistance of the composite plastic. In addition, the hollow zirconium tungstate balls have negative expansion characteristics and will shrink in volume when heated. This volume shrinkage can weaken the volume expansion of the ultra-high molecular weight polyethylene, thereby reducing the degree of thermal deformation of the composite plastic and further improving the high temperature resistance of the composite plastic. Therefore, the thermal deformation temperature of the composite plastic prepared by the present invention is significantly improved compared with that of ultra-high molecular weight polyethylene, so that the composite plastic products can be widely used in high temperature environments.

[0019] In the present invention, the inorganic filler plays a skeleton role in the plastic system and can significantly improve the mechanical properties of the composite plastic. However, if the amount is too high, agglomeration will occur and obvious defects will appear in the system. When subjected to external forces, these defective parts will produce stress concentration, which will reduce the mechanical properties of the material.

[0020] The maleic anhydride grafted polyethylene wax in the present invention can improve the interfacial bonding force between the inorganic filler and the ultra-high molecular weight polyethylene, but if the amount is too much, the macromolecular chain of the maleic anhydride grafted polyethylene wax causes its own molecular chain to entangle, which reduces the interfacial bonding force between the two phases and causes the mechanical properties of the composite plastic to deteriorate. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The ultra-high molecular weight polyethylene (UHMWPE) model used in this application is SLL-2040, purchased from Shanghai Lianle Technology Chemical Co., Ltd., the polyethylene wax is PEW-0320A, purchased from Nanjing Tianshi New Material Technology Co., Ltd., and the remaining raw materials, reagents, instruments and equipment can be purchased from the market or prepared by existing methods.

[0023] Preparation Example 1 The preparation steps of hollow zirconium tungstate spheres are as follows: S1. Dissolve 6 g of anhydrous glucose in 40 mL of deionized water, stir for 30 min, transfer to a hydrothermal reactor with a polytetrafluoroethylene liner, react at 200 ° C for 4 h, cool to room temperature, wash the obtained product with deionized water and anhydrous ethanol by centrifugation for 3 times, and dry the product at 80 ° C for 5 h to obtain carbon spheres; S2. Prepare solution a with a concentration of 0.5 mol / L with zirconium oxychloride octahydrate and deionized water, prepare solution b with a concentration of 1 mol / L with ammonium metatungstate and deionized water, and add 50 mL of solution a and 50 mL of solution b to 25 mL of deionized water under stirring. After the addition is completed, continue stirring for 10 hours, then add 125 mL of 6 mol / L hydrochloric acid solution, heat to reflux reaction for 48 hours, cool to room temperature and remove the supernatant, place the product at room temperature for 7 days, then add 0.6 g of carbon spheres, stir for 1 hour, then place it at rest for 12 hours, centrifuge, and dry the centrifuged product in an oven at 60°C to obtain a precursor powder. Place the precursor powder in a muffle furnace, heat to 500°C at a heating rate of 1°C / min and keep it for 2 hours, then keep it at 610°C for 10 hours, then cool to room temperature with the furnace to obtain zirconium tungstate hollow spheres.

[0024] Preparation Example 2 The preparation steps of hollow zirconium tungstate spheres are as follows: S1. Dissolve 6 g of anhydrous glucose in 60 mL of deionized water, stir for 30 min, transfer to a hydrothermal reactor with a polytetrafluoroethylene liner, react at 200 ° C for 4 h, cool to room temperature, wash the obtained product with deionized water and anhydrous ethanol by centrifugation for 3 times, and dry the product at 80 ° C for 5 h to obtain carbon spheres; S2. Prepare solution a with a concentration of 0.5 mol / L with zirconium oxychloride octahydrate and deionized water, prepare solution b with a concentration of 1 mol / L with ammonium metatungstate and deionized water, and add 50 mL of solution a and 50 mL of solution b to 25 mL of deionized water under stirring. After the addition is completed, continue stirring for 10 hours, then add 125 mL of 6 mol / L hydrochloric acid solution, heat to reflux reaction for 48 hours, cool to room temperature and remove the supernatant, place the product at room temperature for 7 days, then add 0.8 g of carbon spheres, stir for 1 hour, then place it at rest for 12 hours, centrifuge, and dry the centrifuged product in an oven at 60°C to obtain a precursor powder. Place the precursor powder in a muffle furnace, heat to 500°C at a heating rate of 5°C / min and keep it for 2 hours, then keep it at 610°C for 10 hours, then cool to room temperature with the furnace to obtain zirconium tungstate hollow spheres.

[0025] Example:

[0026] A high heat-resistant PE composite plastic comprises the following raw materials in parts by weight: 94 parts of ultra-high molecular weight polyethylene, 3 parts of inorganic filler, 5 parts of maleic anhydride grafted polyethylene wax, and 10100.1 parts of antioxidant.

[0027] The inorganic filler is a composite product of hollow zirconium tungstate spheres and halloysite nanotubes in Preparation Example 1, and the mass ratio of the hollow zirconium tungstate spheres to the halloysite nanotubes is 1:0.1.

[0028] The preparation steps of the maleic anhydride grafted polyethylene wax are as follows: Add 10g polyethylene wax and 100mL xylene into a reactor, heat to 120°C and stir for 5min, add 0.1g benzoyl peroxide and 0.5g maleic anhydride, react at 110°C for 3h, cool to room temperature after the reaction, add 500mL acetone, precipitate, filter, dry the filter cake, grind and sieve, and pass through a 200-mesh sieve to obtain maleic anhydride grafted polyethylene wax.

[0029] The method for preparing the above-mentioned high heat-resistant PE composite plastic comprises the following steps: Ultra-high molecular weight polyethylene, inorganic filler, maleic anhydride grafted polyethylene wax and antioxidant are added to a mixer, stirred at 200 rpm for 30 minutes, and then transferred to a twin-screw extruder for extrusion granulation. The temperature of the first zone of the twin-screw extruder is 135°C, the temperature of the second zone is 160°C, the temperature of the third zone is 165°C, the temperature of the fourth zone is 195°C, the temperature of the fifth zone is 210°C, and the temperature of the sixth zone is 220°C to obtain a high heat-resistant PE composite plastic.

[0030] Example:

[0031] A high heat-resistant PE composite plastic comprises the following raw materials in parts by weight: 91 parts of ultra-high molecular weight polyethylene, 5 parts of inorganic filler, 4 parts of maleic anhydride grafted polyethylene wax, and 10100.3 parts of antioxidant.

[0032] The inorganic filler is a composite product of hollow zirconium tungstate spheres and halloysite nanotubes in Preparation Example 2, and the mass ratio of the hollow zirconium tungstate spheres to the halloysite nanotubes is 1:0.5.

[0033] The preparation steps of the maleic anhydride grafted polyethylene wax are as follows: Add 10g polyethylene wax and 100mL xylene into a reactor, heat to 120°C and stir for 5min, add 0.15g benzoyl peroxide and 0.6g maleic anhydride, react at 110°C for 4h, cool to room temperature after the reaction, add 500mL acetone, precipitate, filter, dry the filter cake, grind and sieve, and pass through a 200-mesh sieve to obtain maleic anhydride grafted polyethylene wax.

[0034] The preparation method of the above-mentioned high heat-resistant PE composite plastic is the same as that of Example 1.

[0035] Example:

[0036] A high heat-resistant PE composite plastic comprises the following raw materials in parts by weight: 88 parts of ultra-high molecular weight polyethylene, 7 parts of inorganic filler, 3 parts of maleic anhydride grafted polyethylene wax, and 10100.1 parts of antioxidant.

[0037] The inorganic filler is a composite product of hollow zirconium tungstate spheres and halloysite nanotubes in Preparation Example 1, and the mass ratio of the hollow zirconium tungstate spheres to the halloysite nanotubes is 1:1.

[0038] The preparation steps of the maleic anhydride grafted polyethylene wax are as follows: Add 10g polyethylene wax and 100mL xylene into a reactor, heat to 120°C and stir for 5min, add 0.2g benzoyl peroxide and 0.7g maleic anhydride, react at 110°C for 5h, cool to room temperature after the reaction, add 500mL acetone, precipitate, filter, dry the filter cake, grind and sieve, and pass through a 200-mesh sieve to obtain maleic anhydride grafted polyethylene wax.

[0039] The preparation method of the above-mentioned high heat-resistant PE composite plastic is the same as that of Example 1.

[0040] Example:

[0041] A high heat-resistant PE composite plastic, compared with Example 1, the only difference is that the weight parts of raw materials are different. The high heat-resistant PE composite plastic in this embodiment includes the following raw materials in weight parts: 94 parts of ultra-high molecular weight polyethylene, 7 parts of inorganic filler, 3 parts of maleic anhydride grafted polyethylene wax, and 1680.5 parts of antioxidant.

[0042] Example:

[0043] A high heat-resistant PE composite plastic, compared with Example 1, the only difference is that the weight parts of raw materials are different. The high heat-resistant PE composite plastic in this embodiment includes the following raw materials in weight parts: 88 parts of ultra-high molecular weight polyethylene, 3 parts of inorganic filler, 5 parts of maleic anhydride grafted polyethylene wax, and 1680.1 parts of antioxidant.

[0044] Comparative Example 1 A high heat-resistant PE composite plastic, compared with Example 1, the only difference is that the "maleic anhydride grafted polyethylene wax" in Example 1 is replaced by an equal weight portion of "maleic anhydride grafted high-density polyethylene (HDPE-g-MAH), powder / ME5506, Nantong Rizhisheng Molecular New Materials Co., Ltd."

[0045] Comparative Example 2 A high heat-resistant PE composite plastic, compared with Example 1, the only difference is that the "maleic anhydride grafted polyethylene wax" in Example 1 is replaced by equal weight parts of "maleic anhydride and polyethylene wax in a mass ratio of 10:0.6, stirred and mixed in a high-speed mixer at a speed of 200 r / min for 20 minutes".

[0046] Comparative Example 3 A high heat-resistant PE composite plastic, compared with Example 1, the only difference is that the "maleic anhydride grafted polyethylene wax" in Example 1 is replaced by an equal weight portion of "polyethylene wax".

[0047] Comparative Example 4 A high heat-resistant PE composite plastic, compared with Example 3, the only difference is that the inorganic fillers in Example 3 are all hollow zirconium tungstate balls of Preparation Example 1.

[0048] Comparative Example 5 A high heat-resistant PE composite plastic, compared with Example 3, the only difference is that the inorganic fillers in Example 3 are all halloysite nanotubes.

[0049] Comparative Example 6 A high heat-resistant PE composite plastic, compared with Example 1, the only difference is that the amount of inorganic filler in Example 1 is adjusted from "3 parts" to "1 part".

[0050] Comparative Example 7 A high heat-resistant PE composite plastic, compared with Example 3, the only difference is that the amount of inorganic filler in Example 3 is adjusted from "7 parts" to "9 parts".

[0051] Comparative Example 8 A high heat-resistant PE composite plastic, compared with Example 4, the only difference is that the amount of maleic anhydride grafted polyethylene wax in Example 4 is adjusted from "3 parts" to "1 part".

[0052] Comparative Example 9 A high heat-resistant PE composite plastic, compared with Example 5, the only difference is that the amount of maleic anhydride grafted polyethylene wax in Example 5 is adjusted from "5 parts" to "7 parts".

[0053] The high heat-resistant PE composite plastics obtained in Examples 1 to 5 and Comparative Examples 1 to 9 were respectively prepared into samples by injection molding using an injection molding machine, and the injection molding temperature was 180-230° C., and then performance tests were performed. The test items are as follows: MFR test: Tested according to ISO 1133-1 / 2:2011, with a load of 2.16kg and a temperature of 230°C. MFR is an indicator that reflects the fluidity of plastic materials in a molten state. It is usually used to evaluate the processing performance of plastics. The larger the MFR, the better the fluidity of the plastic material in a molten state and the better the processing performance. Tensile performance test: tested according to ASTM D638-2003, the tensile rate is 10mm / min; Vera softening temperature test: Tested according to GB / T 1633-2000; The results are shown in Table 1: Table 1

[0054] It can be seen from the data recorded in Table 1 that the high heat-resistant PE composite plastic obtained in Examples 1-5 has an MFR of 5.78-6.20 g / 10 min, a tensile strength of 30.4-34.5 MPa, and a Vera softening temperature of 123.3-127.4° C., and its comprehensive performance is better than that of the high heat-resistant PE composite plastic obtained in Comparative Examples 1-9, indicating that the PE composite plastic prepared by the present invention has good processing performance, high temperature resistance and mechanical properties; Specifically, it can be seen from the test results of Example 1 and Comparative Examples 1, 2 and 3 that replacing "maleic anhydride grafted polyethylene wax" with maleic anhydride grafted high-density polyethylene or maleic anhydride polyethylene wax compound product or polyethylene wax all causes different deteriorations in the processing performance, high temperature resistance and mechanical properties of PE composite plastics; It can be seen from the test results of Example 3 and Comparative Examples 4 and 5 that the comprehensive performance of the obtained PE composite plastic is poor when hollow zirconium tungstate spheres or halloysite nanotubes are used alone as inorganic fillers, indicating that there is a synergistic effect between hollow zirconium tungstate spheres and halloysite nanotubes, and the two together improve the PE composite plastic to have good processing performance, high temperature resistance and mechanical properties; It can be seen from the test results of Example 1 and Comparative Example 6 that the amount of inorganic filler is too low to play a good gain effect, resulting in a significant decrease in the processing performance, mechanical properties and temperature resistance of the PE composite plastic; It can be seen from the test results of Example 3 and Comparative Example 7 that excessive use of inorganic filler will cause agglomeration, resulting in varying degrees of decrease in the processing performance, mechanical properties and temperature resistance of the PE composite plastic; It can be seen from the test results of Example 4 and Comparative Example 8 that the dosage of maleic anhydride grafted polyethylene wax is too low, which makes it difficult to effectively improve the dispersibility of the inorganic filler in the matrix, resulting in poor performance of the obtained PE composite plastic; It can be seen from the test results of Example 5 and Comparative Example 9 that the dosage of maleic anhydride grafted polyethylene wax is too high, and the macromolecular chain of the maleic anhydride grafted polyethylene wax causes its own molecular chain entanglement, which reduces the interfacial bonding force between the two phases and causes the mechanical properties of the composite plastic to deteriorate significantly.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high heat-resistant PE composite plastic, characterized in that: It includes the following raw materials in parts by weight: Ultra-high molecular weight polyethylene 88-94 parts, inorganic filler 3-7 parts, maleic anhydride grafted polyethylene wax 3-5 parts, antioxidant 0.1-0.5 parts; The inorganic filler is a composite product of hollow zirconium tungstate spheres and halloysite nanotubes.

2. A high heat-resistant PE composite plastic according to claim 1, characterized in that: The mass ratio of the hollow zirconium tungstate spheres to the halloysite nanotubes is 1:0.1-1.

3. A high heat-resistant PE composite plastic according to claim 1, characterized in that: The preparation steps of the hollow zirconium tungstate spheres are as follows: Under stirring conditions, solution a and solution b are added dropwise to deionized water at the same time. After the addition is completed, stirring is continued for 10 hours, then hydrochloric acid solution is added, the temperature is raised to reflux reaction for 48 hours, and the supernatant is removed after cooling to room temperature. The product is allowed to stand at room temperature for 7 days, and then carbon balls are added. After stirring for 1 hour, the product is allowed to stand for 12 hours and centrifuged. The centrifuged product is placed in an oven at 60°C to dry to obtain a precursor powder. The precursor powder is placed in a muffle furnace, kept at 500°C for 2 hours and at 610°C for 10 hours, and then cooled to room temperature with the furnace to obtain zirconium tungstate hollow spheres.

4. A high heat-resistant PE composite plastic according to claim 3, characterized in that: The dosage ratio of deionized water, solution a, solution b, hydrochloric acid solution and carbon spheres is 25 mL: 50 mL: 50 mL: 125 mL: 0.6-0.8 g, the concentration of the hydrochloric acid solution is 6 mol / L, solution a is a 0.5 mol / L aqueous zirconium oxychloride octahydrate solution, and solution b is a 1 mol / L aqueous ammonium metatungstate solution.

5. The high heat-resistant PE composite plastic according to claim 3, characterized in that: The preparation steps of carbon spheres are as follows: Anhydrous glucose was dissolved in deionized water, stirred for 30 min, and then transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 200°C for 4 h, cooled to room temperature, and the obtained product was centrifugally washed 3 times with deionized water and anhydrous ethanol respectively, and the product was dried at 80°C for 5 h to obtain carbon spheres.

6. A high heat-resistant PE composite plastic according to claim 5, characterized in that: The usage ratio of anhydrous glucose and deionized water is 6g:40-60mL.

7. The high heat-resistant PE composite plastic according to claim 1, characterized in that: The preparation steps of the maleic anhydride grafted polyethylene wax are as follows: Add polyethylene wax and xylene into a reaction kettle, heat to 120°C and stir for 5 minutes, add benzoyl peroxide and maleic anhydride, react at 110°C for 3-5 hours, cool to room temperature after the reaction, add acetone, precipitate, filter, dry the filter cake, grind and sieve, and pass through a 200-mesh sieve to obtain maleic anhydride grafted polyethylene wax.

8. The high heat-resistant PE composite plastic according to claim 1, characterized in that: The dosage ratio of polyethylene wax, benzoyl peroxide and maleic anhydride is 10g: 0.1-0.2g: 0.5-0.7g.

9. A method for preparing the high heat-resistant PE composite plastic according to any one of claims 1 to 8, characterized in that: The following steps are involved: The ultra-high molecular weight polyethylene, inorganic filler, maleic anhydride grafted polyethylene wax and antioxidant are fully mixed and added into a twin-screw extruder, and extruded into granules to obtain a high heat-resistant PE composite plastic.

10. The method for preparing a high heat-resistant PE composite plastic according to claim 9, characterized in that: The extrusion temperature of the twin-screw extruder is 135-220°C.

Citation Information

Patent Citations

  • High-pressure molded UHMWPE / PA6 (ultrahigh molecular weight polyethylene / polyamide 6) alloy and preparation method thereof

    CN104086848A

  • Hydrothermal synthesis method of nano-scale zirconium tungstate hollow spheres

    CN104495939A

  • Composite polyethylene wax and preparation process thereof

    CN110240777A

  • High-temperature-resistant ultra-high molecular weight polyethylene composite material, pipe and preparation method thereof

    CN112521674A

  • Ultra-high molecular weight polyethylene composition, preparation method thereof, ultra-high molecular weight polyethylene product and application of ultra-high molecular weight polyethylene product

    CN119552434A